2009
DOI: 10.1111/j.1365-2230.2009.03736.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticular variant of mid-dermal elastolysis after insertion of a pacemaker

Abstract: Summary Mid-dermal elastolysis is an unusual process characterized by the absence of the elastic fibres within the mid-dermis. The disappearance of these fibres causes fine wrinkles (type 1) or perifollicular protrusions (type 2) affecting the trunk, neck and arms. There is a female predilection, and most patients have a history of intense sun exposure. Recently, some cases of mid-dermal elastolysis presenting as reticular erythema have been reported. We report a case of reticular erythema with mid-dermal elas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The reticular variant of MDE (type III) was first reported in 2001 by Bannister et al . To the best of our knowledge, five case reports of this variant have been published in the literature . All patients reported were male.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The reticular variant of MDE (type III) was first reported in 2001 by Bannister et al . To the best of our knowledge, five case reports of this variant have been published in the literature . All patients reported were male.…”
Section: Discussionmentioning
confidence: 93%
“…Pathological findings of a loss of elastic fibres limited to mid‐dermis permit the differentiation of these disorders from MDE. The reticular variant of MDE may present similar to reticular erythematous mucinosis, patch stage mycosis fungoides, annular elastolytic giant cell granuloma, actinic granulomas and diffuse granuloma annulare . In fact, some authors have suggested that MDE, granuloma annulare and annular elastolytic giant cell granulomas might represent different stages in the clinical spectrum of dermal elastolysis, with MDE being the late stage of this spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Patients typically present with asymptomatic, well-demarcated, symmetric fine wrinkling of the skin (Type I) and perifollicular papular protrusions (Type II). A third type, an erythematous reticular variant, has more recently been described (Bannister et al, 2001, Cutillas et al, 2010, Gambichler and Lubbe, 2012, Gambichler et al, 2010, Hillen, 2008, Martin et al, 2008, Meyer et al, 2012, Posada et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Finally, there was one report of two male patients with Type III MDE (Meyer et al, 2012). The remainder of the publications were novel cases of Type I and II MDE (Cohen and Tschen, 2013, Cota et al, 2014, Lai et al, 2014, Martinez-Escala et al, 2012) or Type III MDE (Cutillas et al, 2010, Gambichler and Lubbe, 2012, Posada et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“… 6 also reported two men who presented with persistent reticular erythema with focal mid‐dermal elastophagocytosis. Moreover, Cutillas et al 7 described a case of reticular erythema with mid‐dermal elastolysis that occurred in a 70‐year old man after insertion of a pacemaker. Interestingly, all previously reported patients with reticular variant of MDE were males with a median age at diagnosis of 56 years.…”
Section: Introductionmentioning
confidence: 99%